A preliminary study of job stress factors on job satisfaction among government employees in Malaysia's southern region / Nooradzlina Mohd Pauzi … [et al.] - Mohd Pauzi, Nooradzlina; Shari, Asma Shazwani; Ismail, Hadhifah Fadhlina; Luqman, Azyanee; Sakarji, Siti Rosnita; Wan Azib, Wan Nor Hazimah; Subahudin, Siti Nor Aqiliyah (UiTM Press, 2021)
Job stress has become a global problem in recent years, and it is rising year after year. The purpose of this research was to identify influential factors of job stress that affect job satisfaction among the employees in the government sector in the southern region of Malaysia. This research is important because it will help the company determine the best way to assist their workers in improving their job satisfaction. Job stress consists of three elements, namely workload, role conflict, and interpersonal relationships. The questionnaires were distributed to 108 respondents who were employees at Lembaga Kemajuan Johor Tenggara (KEJORA). Descriptive statistics, Cronbach alpha, and regression analysis were employed to analyses the result using the SPSS analysis. The findings revealed that a significant positive relationship exists between interpersonal relationship and job satisfaction whereas role conflict and workload does not influence job satisfaction. Finally, limitations and suggestions for this study are also highlighted.